TWO HERMENEUTICAL TENSIONS IN EVANGELICAL FEMINISM - Poythress, Vern S. (Verbum Christi: Jurnal Teologi Reformed Injili, 2019)
This article shows that there are at least two key hermeneutical tensions in evangelical feminist interpretation of the Bible. The first hermeneutical tension concern the issue of readers' prejudices. Feminists remind us that readers are always disposed to read texts against the background of their own expectations, customs, and world views. And the second hermeneutical tension, namely the tension over the nature of the actual practices of the first century church. Evangelical feminists have tended to give different answers depending on the passage that they are interpreting. In sum, feminism in its hermeneutical principles alerts us to the role of reader prejudice and social background in understanding texts. KEYWORDS: Hermeneutic, feminist, prejudice, Christian